Genetic diversity study in Piper spp. using inter simple sequence repeat (ISSR) markers - K V Saji, P R Rahul, T E Sheeja, G Uma, B Sasikumar, (Journal of Spices and Aromatic Crops, 2013)
Genetic diversity analysis of 27 Piper species using ISSR (Inter Simple Sequence Repeat) markers indicated that the analysis placed them in six clusters in the UPGMA (Unweighted Pair Group Method with Arithmetic Mean) dendrogram. The molecular marker based clustering of the species gave supporting evidence to the earlier groupings proposed by the taxonomists using traditional tools. We have identified 35 species specific bands from different species. P. galeatum had a maximum number of four unique bands.